FACTORS AFFECTING STUDENTS CHOOSING MANAGEMENT STUDY PROGRAM (CASE STUDY ON THE FACULTY OF ECONOMICS AND BUSINESS, Dr. SOETOMO UNIVERSITY, SURABAYA) - Pinaraswati, Sandra Oktaviana; Saibat, Saibat (LPPM ITB AAS INDONESIA (d.h STIE AAS Surakarta), 2020)
The purpose of this study was to examine and analyze: The factors that influence students in choosing a Management study program at Dr. Soetomo University, Surabaya. This research is motivated by a fairly tight competition between private universities in Surabaya to attract students who will continue their studies at higher education, and the large number of study program choices. To win the competition, each private university tries to improve the quality of its study program with various strategies. On the other hand, students have many choices to decide what study program, and which private university to choose. There are certain study programs and private universities that are very popular, and some are less attractive. Therefore, it is very important that the student decision-making process in choosing a study program in a particular private university is analyzed through a study of consumer behavior. Data analysis used is quantitative, while to analyze quantitative data using multiple linear regression analysis. The results showed the R Square coefficient of 0.682 means that variations in student decisions can be explained by the cultural, social, personality, and psychological variables of 68.2%. While the remaining 31.8% can be explained by other variables not examined by this study. Simultaneous testing shows that the independent variables, namely Culture, Social, Personality, Psychology, jointly affect student decisions. This is indicated by the F Count of 61.517. From testing the research variables partially shows that the independent variables, namely Culture, Social, Personality, Psychology, have an effect on the dependent variable, namely Student Decisions. From the independent variables, namely Culture, Social, Personality, the most dominant variable is psychological. This is indicated by the lowest level of significance, namely α = 0.000 and the greatest coefficient, namely the t value of 4.766. Keywords: Culture, Social, Personality, Psychology, Student Decisions